The Time is Ripe for a Consensus Definition of Clinical Recovery in First-episode Psychosis: Suggestions Based on a 10-Year Follow-up Study. (14th April 2022) - Åsbø, Gina; Ueland, Torill; Haatveit, Beathe; Bjella, Thomas; Flaaten, Camilla Bärthel; Wold, Kristin Fjelnseth; Widing, Line; Engen, Magnus Johan; Lyngstad, Siv Hege; Gardsjord, Erlend; Romm, Kristin Lie; Melle, Ingrid; et al.
Abstract: Objectives: A consensus definition of clinical recovery in first-episode psychosis (FEP) is required to improve knowledge about recovery rates in this population. To propose criteria for a future consensus definition, this study aims to investigate rates of clinical recovery when using a standard definition (full psychotic symptom remission and adequate functioning for minimum one year) across both affective and nonaffective FEP groups (bipolar spectrum and schizophrenia spectrum disorders). Second, we aim to explore changes in rates when altering the standard definition criteria. Third, to examine the extent to which healthy controls meet the functioning criteria. Study design: In total, 142 FEP participants and 117 healthy controls preselected with strict criteria, were re-assessed with structured clinical interviews at 10-year follow-up. Study results: A total of 31.7% were in clinical recovery according to the standard definition, with significantly higher recovery rates in bipolar (50.0%) than in schizophrenia spectrum disorders (22.9%). Both groups' recovery rates decreased equally when extending duration and adding affective symptom remission criteria and increased with looser functioning criteria. In healthy controls, 18.8% did not meet the standard criteria for adequate functioning, decreasing to 4.3% with looser criteria. Conclusions: Findings suggest that clinical recovery is common in FEP, although more in bipolar than in schizophrenia spectrum disorders, also when altering the recovery criteria. We call for a future consensus definition of clinical recovery for FEP, and suggest it should include affective symptom remission and more reasonable criteria for functioning that are more in line with the general population.